A comparison of texts and their summaries: Memorial consequences - Reder, Lynne M.; Anderson, John R. (Journal of Verbal Learning and Verbal Behavior, 1980)
Chapters from college textbooks in diverse fields were compared with summaries constructed to convey the main points. A series of studies demonstrate consistent advantages for summaries. Summaries maintained their advantages at retention intervals of 20 minutes, 1 week, and 6 to 12 months. Summaries were superior both for questions directly taken from the text and for inference questions that required the subject to combine facts that had been studied. A transfer task looked at ability to learn new, related material as a function of how the previous material was learned. Summaries yielded better transfer. Reaction time differences showed the same pattern as percentage correct. Summaries maintained their superiority even when the main points in the text were underlined.